Report of Working Group on Water Management for Domestic, Industrial and Other Uses, Government of India - Planning Commission (Planning Commission, 1999)
The "National Commission for Integrated Water Resources Development Plan" was constituted by the Ministry of Water Resources, Government of India in September 1996. the Commission divided the task in nine segments and constituted nine Working Groups with specific expanded terms of reference assigned to each. the Working Group. No. 4 was assigned "Water Management for Domestic Industrial and Other Uses". The composition and the terms of reference of this Working Group are given in Annexures 1.1 and 1.2 respectively. the composition of the Working Group reflects experts from related disciplines who are well known professionals and were selected from the different region of the country having specific knowledge and experience in the development and management issues of the subject matter assigned. Since the Terms of Reference of this Group was quite varied and vast requiring specialised inputs, it was considered necessary to associate Dr. S. Mudgal, Senior Advisor, MOEF and Dr M.A Haque, Additional Director (S), MOEF as special invitees. This facilitated the work considerably the Commission appointed Sh. M.L. Kansal Retd. Chief Engineer, as a full time Resource Person for assisting the Chairman of the Working Group. Approach paper and preliminary report were prepared by the Resource Person of the Working Group. the Group held eleven meetings from time to time. The draft final report of the Group was finalised and presented by the undersigned to the National Commission were it was discussed and deliberated upon thoroughly and based on its observations the report has now been finalised. During its deliberation the Commission transferred a few issues like "Water Quality and Environment" and "Health Related Issues" to Chapter 12 titled "Water Quality and Environmental Aspects" of its report and side by side desired inclusion of issues like "Desalination and water for Recreational Uses" in Chapter 5 titled "Development and Management Issues - Domestic, Industrial and Other Uses" of the Commission's report.
Report of Working Group on Water Management for Domestic, Industrial and Other Uses
Government of India